The performance implications of strategic fit of relational norm governance strategies in global supply chain relationships - Griffith, David A; Myers, Matthew B (Journal of International Business Studies, 2005)
The search for strategic fit has become a core concept in normative models of strategy formation. The issue of strategic fit is becoming increasingly important in global supply chain relationships as managers and academics examine the effectiveness of culturally founded relational governance strategies across multiple supply chain relationships. This study empirically examines the performance implications of strategic fit of relational norm governance strategies in global supply chain relationships between US firms and their primary Japanese and US partners. The performance implications of fitting relational norm governance strategies (i.e., information exchange, flexibility and solidarity) across culturally diverse partners are tested. Results indicate that firm performance is enhanced when the relational norms of information exchange and solidarity are fit to culturally founded norm expectations across culturally diverse relationships simultaneously. Implications for theory and practice are discussed.